Transitional events in the spectrophotometric regime between stripped envelope and superluminous supernovae - Prentice SJ; Inserra C; Schulze S; Nicholl M; Mazzali PA; Vergani SD; Galbany L; Anderson JP; Ashall C; Chen TW; Deckers M; Mancheno MD; et al. (OXFORD UNIV PRESS, 2025)
The division between stripped-envelope supernovae (SE-SNe) and superluminous supernovae (SLSNe) is not well-defined in either photometric or spectroscopic space. While a sharp luminosity threshold has been suggested, there remains an increasing number of transitional objects that reach this threshold without the spectroscopic signatures common to SLSNe. In this work, we present data and analysis on four SNe transitional between SE-SNe and SLSNe; the He-poor SNe 2019dwa and 2019cri, and the He-rich SNe 2019hge and 2019unb. Each object displays long-lived and variable photometric evolution with luminosities around the SLSN threshold of M-r < -19.8 mag. Spectroscopically however, these objects are similar to SE-SNe, with line velocities lower than either SE-SNe and SLSNe, and thus represent an interesting case of rare transitional events.